THE ROLE OF PARENTS IN FORMING CHILDREN'S STUDY HABITS AT HOME - Komari Komari; Emon Paranoan; Upi Laila Hanum; Merliana Trince (Adisam Publisher, 2025)
This literature review was conducted by identifying and analyzing various studies related to the role of parents in children's education at home. The findings indicate that parental involvement is positively correlated with children's learning outcomes. Effective strategies include creating a conducive learning environment at home, adapting learning strategies according to children's learning styles, and education on time management and independent learning skills. Findings also show the importance of supportive parental attitudes and positive expectations of children's education in fostering motivation and effective learning. Parents who are flexible in their educational methods and are able to adapt to their children's needs seem to be more successful in developing independent and adaptive learners.